An investigation of financial performance on operations of Croco motors service stations - Kavhai, Auline (Midlands State University, 2017)
This study was motivated by consecutive losses that were being reported by Croco Motors Service Stations. The study covered the period from 2012 to 2014. The main objective of the study was to investigate the financial performance on the operations of Croco Motors Service Stations. The research sought to establish the financial performance policy and financial performance guidelines in place, assess personnel capacity, identify challenges being faced, examine controls in place and determine the best practices that can be adopted by Croco Motors as an organisation. Literature from different authors in relation to the study was discussed. Descriptive research method was employed and data instruments used to collect data were questionnaires and interviews. The researcher used a census of the target population and the response rate was 83% (23). The respondents included Directors, Finance department, Workshop department, Internal Audit department, Marketing department and Customer services department. Data was presented in tables and graphs. A statistical modal analysis technique was used to analyse data. The results of the study showed that Croco Motors has a financial policy but it is not documented and not adhered to, financial performance guidelines are in place, personnel are inadequate and not suitably qualified. Financial performance challenges faced by Croco Motors Service Stations include high operational costs, decline in revenue, stiff competition, reduction of clientele base, management incompetence and over expansion. The internal control is weak. The research recommended documentation of financial policy and adherence to it, hiring of adequate personnel that are competent, implementation of profit and survival strategies for example costs cutting, implementation of a sound internal control system and adoption of the following best practices; improved marketing practices, revised strategic planning, budgetary control, management audit, management of information systems, benchmarking performance, risk management, people and performance management. Further research maybe undertaken on the implementation of viable costs cutting initiatives on a firm’s operations.